Dari Kuas ke Kode: Transformasi Seni di Era AI - Nurfitrianah Octavianingrum Raharjo Putri; Dewi Hermanden; Karna Mustaqim (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
This study examines the transformation of visual art practices in the era of artificial intelligence, particularly through text-to-image generative technologies. The research aims to analyze differences between manually created artworks and AI-generated images, focusing online quality, visual logic, and color application. A qualitative descriptive approach based on practice-based research was employed. The researcher produced watercolor paintings as primary references and then recreated them using AI platforms such as ChatGPT and Gemini through structured prompts. The findings indicate that AI demonstrates strong capabilities in producing visually realistic compositions with aesthetically pleasing color harmonies. However, AI-generated images tend to exhibit compositional inconsistencies, random variations, and the addition of unintended elements. In terms of line quality, AI lacks gestural expressiveness and fails to reflect artistic intention. Similarly, while color outputs appear harmonious, they often lack emotional depth and contextual sensitivity. These results suggest that AI operates based on generative logic rather than intentional artistic reasoning. Therefore, although AI can function as a supportive tool in visual exploration, the role of human artists as creators of meaning and aesthetic experience remains irreplaceable.